Learning of Renewable Energy Sources in Elementary School Based on Digital - Abdul Rohman; Asep Bayu Dani Nandiyanto (Open Global Scientific Journal, 2022)
The purpose of this study was to analyze the understanding and knowledge of energy sources from the definition, types and benefits of using digital-based learning methods. This research was conducted on grade elementary school students in the city of Pandeglang, Indonesia using 20 question questionnaires as the object of assessment, the questionnaire was distributed at the first meeting and continued with material at the next meeting then at the final meeting the students would fill out the questionnaire again. The same as the evaluation material. The question questionnaire was distributed through social media such as whatsapp and manually using writing paper. These results indicate that the scores obtained by the students showed an increase. This proves that the students already know the basic material that has been given and understand the material that has been taught at the previous meeting. The material taught about renewable energy sources is the meaning of renewable energy, types of renewable energy, the use of renewable energy and how to save energy. The main reason for the success in this research is that the material is given to students using powerpoint media which is packaged in an attractive way so that students are enthusiastic about learning, besides that, each meeting will be filled with discussion sessions and activities to watch learning videos obtained through YouTube media which aims to to increase students’ knowledge about renewable energy sources. With this learning method, students are more enthusiastic in doing learning as evidenced by students who are actively answering the questions that have been asked.